Butyrate, neuroepigenetics and the gut microbiome: Can a high fiber diet improve brain health?. (20th June 2016) - Bourassa, Megan W.; Alim, Ishraq; Bultman, Scott J.; Ratan, Rajiv R.
Highlights: Interest in how diet influences brain function via the gut microbiome is growing. Butyrate can protect the brain and enhance plasticity in neurological disease models. Gut microbiota produce butyrate by fermenting carbohydrates in a high fiber diet. Hypothesis: A high fiber diet can elevate butyrate to prevent/treat brain disorders. Abstract: As interest in the gut microbiome has grown in recent years, attention has turned to the impact of our diet on our brain. The benefits of a high fiber diet in the colon have been well documented in epidemiological studies, but its potential impact on the brain has largely been understudied. Here, we will review evidence that butyrate, a short-chain fatty acid (SCFA) produced by bacterial fermentation of fiber in the colon, can improve brain health. Butyrate has been extensively studied as a histone deacetylase (HDAC) inhibitor but also functions as a ligand for a subset of G protein-coupled receptors and as an energy metabolite. These diverse modes of action make it well suited for solving the wide array of imbalances frequently encountered in neurological disorders. In this review, we will integrate evidence from the disparate fields of gastroenterology and neuroscience to hypothesize that the metabolism of a high fiber diet in the gut can alter gene expression in the brain to prevent neurodegeneration and promote regeneration.